2020
DOI: 10.1021/acscatal.0c02716
|View full text |Cite
|
Sign up to set email alerts
|

Development of Brønsted Base–Photocatalyst Hybrid Systems for Highly Efficient C–C Bond Formation Reactions of Malonates with Styrenes

Abstract: Brønsted base−photocatalyst hybrid systems have been developed for reactions of malonates with styrene derivatives. The concept of this process lies in the photo-oxidation of catalytic amounts of the enolate to form reactive radicals that react with alkene double bonds under mild reaction conditions. This is an example of visible-light-activated C−C bond formation reactions of malonates with alkenes to realize high atom economy under very mild reaction conditions without using any transition-metal catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…In 2020, Yamashita, Kobayashi, and Baś reported a C(sp 3 )–H alkylation reaction between malonate diesters and styrenes via generation and addition of a 1,3-dicarbonyl radical across the alkene acceptor ( Scheme 162 ). 466 Optimal conditions consisted of photocatalyst 4CzIPN , or the related 3DPA2FBN , and KO t -Bu Brønsted base co-catalyst in MeCN solvent under blue-light irradiation. The authors reported 33 examples of this transformation with yields ranging from 17% to 99%.…”
Section: O -Centered Radical Generation From O–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…In 2020, Yamashita, Kobayashi, and Baś reported a C(sp 3 )–H alkylation reaction between malonate diesters and styrenes via generation and addition of a 1,3-dicarbonyl radical across the alkene acceptor ( Scheme 162 ). 466 Optimal conditions consisted of photocatalyst 4CzIPN , or the related 3DPA2FBN , and KO t -Bu Brønsted base co-catalyst in MeCN solvent under blue-light irradiation. The authors reported 33 examples of this transformation with yields ranging from 17% to 99%.…”
Section: O -Centered Radical Generation From O–h Bonds Through Photochemical and Electrochemical Pcet Processesmentioning
confidence: 99%
“…In 2020, they reported a dual catalytic system of Brønsted base and visible light for the reaction of malonate with less electrophilic olefins (Scheme 53). The alkylation reaction is of mild transition metal free condition and high atom economy [201] . First, the photocatalyst was excited by visible light to generate [PC]*, which oxidized the enol form 160 to excited state 161 .…”
Section: Combining Brønsted Base Catalysis With Photoredox Catalysismentioning
confidence: 99%
“…The alkylation reaction is of mild transition metal free condition and high atom economy. [201] First, the photocatalyst was excited by visible light to generate…”
Section: Combining Brønsted Base Catalysis With Photoredox Catalysismentioning
confidence: 99%
“…Very recently, the group of Yamashita and Kobayashi developed a C−C coupling reaction between malonates and styrenes [56] . The reactions were performed at room temperature in MeCN as the solvent under irradiation with blue LEDs (Scheme 42).…”
Section: Cyanoarene‐based Organophotocatalystsmentioning
confidence: 99%